Reading Proficiency Levels in English among the Intermediate Graders in Manito District SY 2022-2023 - Maria Jellie Obar (Philippine Association of Institutions for Research, Inc., 2023)
This study aimed to determine the reading proficiency levels in English among intermediate graders in the Manito District, as well as the factors that affect these levels. The research design utilized for this study is descriptive-correlational, which describes the relationship between the factors and the reading proficiency in English of the intermediate graders. The four categories of factors that were explored in this study were pupil factors, teacher factors, home factors, and curriculum factors. The research findings indicated that pupil factors such as vocabulary, comprehension, and word recognition impact intermediate graders' reading proficiency levels in English. Home factors such as parental involvement, access to reading materials, and socioeconomic status also contribute to the development of reading proficiency. Teacher and curriculum factors had no significant relationship with reading proficiency levels in English. By addressing the identified factors, parents can be provided with support, and pupils can be given reading materials to create a home learning environment that promotes literacy development. A contextualized illustrated short stories and workbook as supplementary reading material was developed to improve reading proficiency levels in English among intermediate pupils.